Students' Perception on the Discovery Learning Strategy on Learning Reading Comprehension at the English Teaching Study Program Christian University of Indonesia - Tampubolon, Daniel (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2017)
Abstract The main objectives of this study are to discover and examine the students’ perception on the use of discovery learning strategy on reading comprehension and to see whether the students are interested in using discovery learning strategy on improving their reading comprehension. This study is a survey research. This study was conducted to all students of the English Teaching Study Program (ETSP), Christian University of Indonesia. To achieve the objectives, data were collected using questionnaire and interviews. The data was analyzed descriptively through Microsoft Excel 2007. Based on the data analysis, it can be concluded that the majority of students agreed that discovery learning strategy can enhance their reading comprehension and they want this strategy implemented in their reading class. Furthermore, they were interested on learning or improving reading comprehension through discovery learning strategy. Keywords: reading comprehension, discovery learning strategy, perception